Tincup [large type] - Rundell, B. N. (Rundell, B. N. Quest chronicles, 2025)
"Still reeling from the aftermath of a brutal attack that shattered his family and razed his home to ashes, Cordell Beckett emerges from the wreckage transformed. It took three years to make a man out of a boy, but that man has begun his chase and now finds himself in the gold fields of the Wild West. With his loyal dog by his side and the vast expanse of the frontier stretching out before him, Cordell casts a long shadow over the trail, his presence striking fear into the hearts of outlaws. Yet, as he draws closer to his quarry, doubt gnaws at him. Will he succeed in his quest for vengeance ... or will he falter at the threshold of his life's purpose? -- Back cover.